Technical Problems in the Renovation of Historic Bridges. Case Study - Road Bridge in Cigacice - Mielczarek, Magdalenia; Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The road bridge in Cigacice is a very good example of and testimony to the level of knowledge and skills in interwar engineering art. The bridge is almost 100 years old, put to use in 1925, and was designed and manufactured by Beuchelt & Co. in Zielona Góra. The bridge has 10 spans with a parabolic main span, and the supporting structure for the spans is made of steel lattice girders. The object has been strengthened and modernized several times. Currently, renovation works are also being carried out, resulting from identified unfavorable corrosion of the steel elements of the bridge and the concrete bridge slab. The historic steel structure and the bridge supports are being renovated according to the conservation recommendations.
Keywords: road bridge; renovation; cultural heritage preservation; Cigacice; bridges; Oder river; most drogowy; renowacja; ochrona dziedzictwa kulturowego; Cigacice - most; Odra